PENGARUH KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL MEDIASI PENGHIDARAN PAJAK PADA PERUSAHAAN PROPERTY - Andriyani, Jesica; Hutabarat, Francis (JURNAL AKUNTANSI DAN INVESTASI, 2020)
The aim of this study is to analyze the factors influencing the company's valuation in the IDX sub-sector companies in the real estate and real estate sectors. In this analysis, the mechanism is quantitative. The data used is secondary data in the form of annual financial reports from 8 Property & Real Estate Sub Sector Companies. Dividend Pay out Ratio or DPR (X1), Cash Effective Tax Rates or Cash ETR (X1), and Firm Value or Q (Y) are study variables. Path analysis is the data analysis approach used. Model 1 test results show that the dividend policy (DPR) has no influence on Q with a significant value (-0.301> 0.212) and tax avoidance (Cash ETR) has no effect on Q with a significant value (-0.023> 0.034). The results of the Model 2 test explain that with a meaning of significance (0.046> 3.95), dividend policy (DPR) affects tax avoidance (Cash ETR). It can be inferred, on the basis of the research findings, that the existence of tax avoidance totally mediates the effect of the dividend policy on firm valuation.